ANALISIS KESEHATAN BANK MENGGUNAKAN METODE RGEC PADA PT.BANK MANDIRI (PERSERO) TBK. - Muhammad Dava Rizki Haliq (2022)
This stuify is aimed to determining bank heatth level trough Risk Profile, Good Corporate Governance, Earnings, Capita/ (RGEC) Method at Bank Mandiri. The type of the research was descriptive research using quantitative approach. The Variables and measurements in this research were Risk Profile factor. Good Corporate Governance factor. Earning factor, and Capital factor. The results showed that bank health level at Bank Mandiri in 2017 until 2021 method by RGEC overall was in the first place of composite ranked with a very healthy. The bank health level was the most important thing that might be considered by the management of the bank because it was an indicator of the customers to be able to entrust their funds to a bank Therefore, the main task of the Bank Mandiri was always maintaining the trust of our customers try continuously improving the effectiveness and efficiency in accordance with the vision and mission of the company. Keyword : Bank Health level. Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) Method.